Epigenetic screen identifies genotype-specific promoter DNA methylation and oncogenic potential of CHRNB4 - Scherf, David; Sarkisyan, N.; Jacobsson, Hanna; Claus, R.; Lorenzo Bermejo, Justo; Peil, B.; Gu, L.; Muley, Thomas; Meister, Michael; Dienemann, Hendrik; Plass, Christoph; Risch, Angela (Oncogene, 2013)
Genome-wide association studies have highlighted three major lung cancer susceptibility regions at 15q25.1, 5p15.33 and 6p21.33. To gain insight into the possible mechanistic relevance of the genes in these regions, we investigated the regulation of candidate susceptibility gene expression by epigenetic alterations in healthy and lung tumor tissues. For genes up or downregulated in lung tumors, the influence of genetic variants on DNA methylation was investigated and in vitro studies were performed. We analyzed 394 CpG units within 19 CpG islands in the susceptibility regions in a screening set of 34 patients. Significant findings were validated in an independent patient set (n=50) with available DNA and RNA. The most consistent overall DNA methylation difference between tumor and adjacent normal tissue on 15q25 was tumor hypomethylation in the promoter region of CHRNB4 with a median difference of 8% (P<0.001), which resulted in overexpression of the transcript in tumors (P<0.001). Confirming previous studies, we also found hypermethylation in CHRNA3 and telomerase reverse transcriptase (TERT) with significant expression changes. Decitabine treatment of H1299 cells resulted in reduced methylation levels in gene promoters, elevated transcript levels of CHRNB4 and CHRNA3, and a slight downregulation of TERT demonstrating epigenetic regulation of lung cancer cells. Single-nucleotide polymorphisms rs421629 on 5p15.33 and rs1948, rs660652, rs8040868 and rs2036527 on 15q25.1, previously identified as lung cancer risk or nicotine-addiction modifiers, were associated with tumor DNA methylation levels in the promoters of TERT and CHRNB4 (P<0.001), respectively, in two independent sample sets (n=82; n=150). In addition, CHRNB4 knockdown in two different cell lines (A549 and H1299) resulted in reduced proliferation (PA549<0.05;PH1299<0.001) and propensity to form colonies in H1299 cells. These results suggest epigenetic deregulation of nicotinic acetylcholine receptor subunit (nAChR) genes which in the case of CHRNB4 is strongly associated with genetic lung cancer susceptibility variants and a functional impact on tumorigenic potential.
Published online 3 September 2012
Gesehen am 07.02.2022